2006
DOI: 10.1073/pnas.0601113103
|View full text |Cite
|
Sign up to set email alerts
|

Water dynamics and salt-activation of enzymes in organic media: Mechanistic implications revealed by NMR spectroscopy

Abstract: Deuterium spin relaxation was used to examine the motion of enzyme-bound water on subtilisin Carlsberg colyophilized with inorganic salts for activation in different organic solvents. Spectral editing was used to ensure that the relaxation times were associated with relatively mobile deuterons, which were contributed almost entirely by D2O rather than hydrogen-deuteron exchange on the protein. The results indicate that the timescale of motion for residual water molecules on the biocatalyst, ( c)D 2 O, in hexan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 42 publications
2
47
0
Order By: Relevance
“…It is noteworthy that numerous previous studies, including a recent study by our laboratory (33), provide evidence of correlations between fast solvent dynamics and molecular events evident on slower timescales [e.g., substrate dissociation in myoglobin (34); protein folding of cytochrome c, protein L, and human serum albumin (35,36); and enzyme activity (37,38)]. The intimate collusion between fast solvent dynamics and slow protein motion is referred to as solvent slaving and has been reported for many classes of proteins (39,40).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that numerous previous studies, including a recent study by our laboratory (33), provide evidence of correlations between fast solvent dynamics and molecular events evident on slower timescales [e.g., substrate dissociation in myoglobin (34); protein folding of cytochrome c, protein L, and human serum albumin (35,36); and enzyme activity (37,38)]. The intimate collusion between fast solvent dynamics and slow protein motion is referred to as solvent slaving and has been reported for many classes of proteins (39,40).…”
Section: Resultsmentioning
confidence: 99%
“…Further study of this water population indicated that the amount and motion of the residual water molecules associated with the biocatalyst correlated strongly with biocatalyst activity in an Arrhenius-like fashion, with residual water molecules in salt-activated biocatalysts exhibiting shorter correlation times for motion in the more active salt preparations (33). These water molecules exhibited correlation times in the picosecond-to-nanosecond time regime.…”
Section: Resultsmentioning
confidence: 99%
“…K + does not change the affinity of IMP. Interestingly, water and salt are believed to act as molecular lubricants to increase enzyme activity in organic solvents 148. Perhaps K + activates IMPDH by similarly facilitating the interchange of conformations.…”
Section: Mechanismmentioning
confidence: 99%
“…The mechanism explaining the rapid release of CO 2 to the atmosphere is not well understood (Halverson et al, 2000). The potential explanations include the release of intracellular solutes to the environment by soil bacteria due to the disruption of cell membranes or cell lysis under the dramatic difference in water potential after rain (Halverson et al, 2000), the physical displacement of percolating water with CO 2 built up during the previous dry period (Huxman et al, 2004), the rapid catabolism of low molecular weight carbohydrates or other labile carbon solutes to CO 2 , the rapid increase of microbial activity (Fierer and Schimel, 2002;Saetre and Stark, 2005;Xu et al, 2004), and the increased effectiveness of enzymes and consequent reduction in Ea (active energy) (Daniel et al, 2003;Eppler et al, 2006). In a system that has not experienced rainfall for some time, where physiological activity is very low, rainfall first triggers a burst of positive CO 2 flux, caused by the combination of mechanisms discussed above.…”
Section: Analysis Of Influential Factors On Co 2 Effluxmentioning
confidence: 99%